Empirical process of the squared residuals of an ARCH sequence - Lajos Horvath; Piotr Kokoszka; Gilles Teyssière (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
We show that the empirical process of the squared residuals of an ARCH(p) sequence converges in distribution 1,0 a Gaussirm process B(F(t)) +t f(t) e, where F is the distribution function of the squared innovations, f its derivative, B(tl, 0 <; t>1 a Brownian bridge and e a normal random variable.
urn:nbn:de:kobv:11-10046737
Keywords: 330; ARCH model; empirical process; squared residuals